2021
DOI: 10.1111/anae.15353
|View full text |Cite
|
Sign up to set email alerts
|

Using psychometric ability to improve education in ultrasound‐guided regional anaesthesia: a multicentre randomised controlled trial

Abstract: The learning curve for novices developing regional anaesthesia skills, such as real-time ultrasound-guided needle manipulation, may be affected by innate visuospatial ability, as this influences spatial cognition and motor coordination. We conducted a multinational randomised controlled trial to test if novices with low visuospatial ability would perform better at an ultrasound-guided needling task with deliberate practice training than with discovery learning. Visuospatial ability was evaluated using the ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The underlying framework of visuospatial ability can be used in various ways to improve US education. Chuan et al [ 52 ] showed that if medical students with low visuospatial ability receive extra training in mental rotation, they can achieve the same UGRA performance scores as their fellow students with higher visuospatial abilities. Furthermore, Hewson et al [ 55 ] specifically trained students’ mental rotation with a simple task and improved UGRA performance.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying framework of visuospatial ability can be used in various ways to improve US education. Chuan et al [ 52 ] showed that if medical students with low visuospatial ability receive extra training in mental rotation, they can achieve the same UGRA performance scores as their fellow students with higher visuospatial abilities. Furthermore, Hewson et al [ 55 ] specifically trained students’ mental rotation with a simple task and improved UGRA performance.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional modified radical mastectomy involves the induction of general anesthesia to relieve pain [18,19]. Although general anesthesia plays a certain inhibitory role in the limbic system of the cerebral cortex, it cannot block the conduction of peripheral noxious stimuli to the central nervous system, thereby promoting stress responses in patients during surgery [7,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…A pork meat phantom with embedded bovine tendon was constructed as per our previous work [6,7]. This phantom closely resembles human nerve and muscle structures under ultrasound and allowed us to capture ultrasound images of needles inserted at multiple angles.…”
Section: Methodsmentioning
confidence: 99%
“…Novice participants were shown a 10-min training video previously used in our work [6,7] that explained the fundamentals of ultrasound physics, transducer movements and in-plane needle guidance under ultrasound. All participants were orientated to the virtual reality equipment and then allowed to explore the virtual reality trainer environment to familiarise themselves with the motion controllers and ultrasound scan the virtual patient.…”
Section: Methodsmentioning
confidence: 99%